THE THEORETICAL-METHODOLOGICAL CONCEPT OF THE SPECIAL TESTIMONY AND THE PROBLEM OF THE MARGINALITY OF CHILDREN'S VOICES - Santos, Jonathas Ferreira; do Nascimento Osório, Antônio Carlos (Seven Editora, 2025)
This article analyzes the theoretical-methodological conception of the “depoimento especial” (special testimony) in the Brazilian judicial system, critically examining the limits and contradictions of hearing children and adolescents who are victims or witnesses of violence. Drawing on Critical Legal Psychology, childhood epistemology and human-rights studies, it argues that the historical marginalization of children’s voices persists even within supposedly protective practices. The study frames the special testimony as a juridical device that emerged to protect children and adolescents, yet, from a Foucauldian perspective, reveals the rationalities and discourses that actually sustain the current institutional model and question the alleged centrality granted to children’s narratives. The analysis shows that, despite a protective rhetoric, an underlying structural marginalization remains—especially when punitive and technical interests prevail over a qualified, ethical listening attuned to the historical, social and affective singularities of each child. The article advocates for an approach to listening that transcends mere procedural technique, embracing children as historical subjects whose voices deserve full recognition and respect.DOI: https://doi.org/10.56238/sevened2025.029-073